Evaluasi Eko-Teknis Struktur Habitat Lamun dan Kelimpahan Echinodermata di Pulau Pahawang - Nurdiana Nurdiana; Anna Ida Sunaryo Purwiyanto; Riris Aryawati; Isnaini Isnaini; Hartoni Hartoni (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
Seagrass ecosystems serve as important habitats for various marine organisms, including Echinodermata. This study aims to examine the relationship between seagrass cover and the abundance of Echinodermata in the waters of Pahawang Island. Sampling was conducted at four stations using the transect–quadrat method, followed by species identification and measurements of seagrass cover. Three seagrass species were recorded: Enhalus acoroides, Thalassia hemprichii, and Halodule uninervis. Eight species of Echinodermata from four classes were found, with Diadema setosum being the most abundant and occurring at all stations. Other species appeared selectively, depending on local habitat conditions. Higher Echinodermata abundance was observed in areas with greater seagrass cover. Regression analysis revealed a positive relationship between seagrass cover and Echinodermata abundance, indicating that denser seagrass beds support higher population levels. Overall, the condition of seagrass ecosystems plays a key role in shaping the abundance and distribution of Echinodermata, highlighting the importance of conserving seagrass habitats around Pahawang Island.